MICROENCAPSULATION OF ANCHOVY (ENGRAULIS ENCRASICOLUS L.) OIL: EMULSION CHARACTERIZATION AND OPTIMIZATION BY RESPONSE SURFACE METHODOLOGY - Tatar, Feyza; Kahyaoglu, Talip (WILEY, 2015)
The aim of the present study was to evaluate the anchovy (Engraulis encrasicolus L.) oil emulsion characterization and to optimize the anchovy oil microencapsulation process by spray drying. Response surface methodology was employed to study the effects of inlet air temperature (160-190C), peristaltic pump rate (20-40%) and ratio of coating to oil (2/1-4/1) on the oil particle size, microencapsulation efficiency (MEE), peroxide value (PV), bulk density, Carr index (CI) and dry matter. The inlet air temperature showed a significant (P < 0.05) influence on the MEE, PV and CI of samples. The peristaltic pump rate and ratio of coating to oil affected significantly (P < 0.05) only the MEE and PV. The optimal drying condition for microencapsulation of anchovy oil was found as 164C the inlet air temperature, 25% the peristaltic pump rate and 4/1 the ratio of coating to oil.
Keywords: FISH-OIL; OXIDATIVE STABILITY; ENCAPSULATION; CHITOSAN; Food Science & Technology